Comparison of PID and Fuzzy Controller for Position Control of AR.Drone - A Prayitno; V Indrawati; I I Trusulaw (IAES Indonesia Section, 2016)
This paper describes the implementation of the PID Controller to control the position of the AR.Drone in the x-y-z. This position control scheme uses three PID controllers to maintain the position of x, y and z using the signal control pitch, roll and vertical rate. PID Controller implemented on AR.Drone 2.0 and then tested in an indoor space. The performance of the controller will be compared with Fuzzy Logic Controller schemes that have been implemented previously. The results show that the PID Controller generate a response with rise time less than 3 seconds at the x and y position with around 25% overshoot. The result for z position give better result without overshoot. The comparison between fuzzy logic and PID Controller indicates that the results of the PID controller is better although there is overshoot.